Obesogenic eating behaviors mediate the relationships between psychological problems and BMI in children. Issue 5 (29th March 2017) - Mallan, Kimberley M.; Daniels, Lynne A.; Nicholson, Jan M.
Abstract : Objective: To examine the association between psychological problems and weight status in children aged 3.5 to 4 years and test whether obesogenic eating behaviors mediate this relationship. Methods: This study is a cross‐sectional secondary analysis of data from first‐time mothers ( N = 194) in the control arm of the NOURISH randomized controlled trial. At child age 3.5 to 4 years, maternal‐reported child eating behaviors and psychological problems were collected via valid tools, and child weight and height data were collected by trained study staff. Pearson's correlations and linear regressions examined associations between eating behaviors, psychological problems, and BMI z score. Multiple mediation models were tested by assessing indirect effects of psychological problems on BMI z score via obesogenic eating behaviors. Results: Peer problems were associated with both higher food responsiveness and emotional overeating and directly with higher BMI z score. This relationship was partially mediated by emotional overeating. Both emotional overeating and food responsiveness fully mediated the association between emotional problems and BMI z score, and food responsiveness fully mediated the association between conduct problems and BMI z score. Conclusions: The findings suggest that children with psychological problems may also display obesogenic eating behaviors, which may result in higher BMI. This needs to be considered in the clinical management of both pediatric overweight/obesity and psychological problems.